(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article deals with construction precast and precast with cast-in-place frame buildings, which elements’ combined action is provided by key joints, are widely used. The paper is devoted to the key joints, taking up considerable transverse forces. Standard methods of their calculation are imperfect, they do not take into account all factors of influence and cause significant underestimation of the joint’s strength. At Poltava National Technical Yuri Kondratyuk University a calculation methodology has been developed, which, being generic enough, takes into account the destruction’s character and a set of influence factors. Three- and five-key joints of multi-storey building’s reinforced concrete frame’s elements have been considered. An example is given of determining the strength of the capillary’s joint with the column of the precast flat slab floor by means of the variational method in the concrete plasticity theory. The obtained results are compared to the standard calculations. Keywords: joint, key, strength, plasticity, shear, concrete.